ICT for governance in combating corruption: the case of public e-procurement in Portugal - Ferreira, Isabel (2018)
Literature has highlighted the potential of information and communication technology (ICT) in building new models of public governance that promote fairness and accountability, which are key requirements in the fight against corruption. In this context, it is worth mentioning the sector of public procurement, since it is one of the most sensitive concerning any corruption risk. There have been a number of investments by governments towards the implementation of public e-procurement. Portugal is referenced by the European Commission as a good example in this regard. The question that arises is whether this would have an impact on the degree of trust between the citizens and governance, i.e. regarding perception of corruption. This paper explores the theme "ICT governance and transparency in the fight against corruption - the case of public e-procurement in Portugal." Thus, the aim is to discuss the abovementioned issue with a view in developing future investigations.